ℋ∞ Control for Differential-Algebraic Systems. Issue 2 (2020) - Sperilă, Andrei; Tudor, Florin S.; Ciubotaru, Bogdan D.; Oară, Cristian
Abstract: For a differential-algebraic system, we construct the class of proper suboptimal H ∞ stabilizing controllers and give formulas in terms of realizations and solutions to appropriate Riccati equations.